Method for In Situ On-Wafer Tensile Test of Thin Films - Xufeng Wang; Jiakang Li; Yi Chen; Jiawei Zhou; Leijian Cheng; Dacheng Zhang (Micromachines)
This study addresses the need for a mechanical property characterization of films during Micro-Electro-Mechanical System (MEMS) processing by proposing a novel in situ on-wafer tensile strength testing method for film materials. This method integrates the film specimen with a bulk silicon test structure during fabrication, allowing for tensile strength measurements with a resolution of 0.05 MPa using only a probe and optical microscope. Utilizing this method, we successfully performed in situ on-wafer tensile strength tests on Al films of various sizes, demonstrating the impact of the process on film mechanical properties. The results validate the potential of this structure for characterizing material mechanical properties and monitoring process quality in mass production.